FLOOR ELEVATION SHAPE MEANING WITH VASTU AS CONTEXT IN WITANA WARD, YOGYAKARTA PALACE - Ajeng Kusuma; Tarcicius Yoyok Wahyu Subroto (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2023)
The fact that the Yogyakarta Palace is a centre and means of embodying cultural values that are still maintained and exist is proven through two aspects intangibles and tangibles. The distribution of local values reality, such as philosophy increasingly being threatened among the younger generation. From the physical revitalisation, we can understand the symbolic meaning of the Yogyakarta Palace through buildings because they contain complete symbolic meanings, especially in Witana Ward's floor elevation. What is the floor elevation shape with the steps? How is the relationship process between geometric shapes and symbolic meanings? What is the symbolic meaning of the floor elevation shape with steps? The research questions align with the urgency to formulate floor elevation shapes with the steps, formulate a relationship process between geometric shapes and symbolic meanings, and formulate the symbolic meaning of the floor elevation shape. The semiotic method with Peirce and Chandler's analytical model will be applied to study the floor elevation forms to uncover latent factors that are produced by truths under local knowledge. The result is a system consisting of three sign components, built from floor elevation shape with the steps objects that have a relationship with Vastu as context.